Improvement of The Operation for KOPIBIKE Restaurant Using Menu Engineering Approach - Adeng, Rachmadi; Firman, Aries F. (The Indonesian Journal of Business Administration, 2013)
In the food business today, having a list of regular customers is not enough to remain successful. One of the key is needs a well performed sales mix analysis and pricing strategies to keep the food businesses thriving. For this analysis it can be used Menu Engineering which provide calculating the sales and it’s constribution margin, and categorizing it. From the aspect of Operation Management restaurant need to control their inventory, a complete listing of their stock of raw materials and components, works in progress and finished products. The purpose of inventory control is to efficiently manage the availability of stock for production, sales and delivery and services of a business to maximize the volume of business and profits. This final project is focused on how the menu engineering result can change the menu design and it’s component with the aim of improving profitability and improvement on inventory management in the restaurant can support effective and efficient business process in order to delight customers by fulfilling their demand. Keywords: Availability of Stock, Menu Engineering, Operation Management